Obstacles of graduates in hiring job / Tuan Safa'at Tuan Ameri - Tuan Ameri, Tuan Safa'at (Faculty of Information Management, 2014)
Everyone has barriers to employment. Same goes to fresh graduates. Most of the graduates probably have few barriers onto themselves and preventing them from daring themselves to new levels of greatness. It is important for the graduates to realize and clarify that whenever they find themselves resisting anything during the dream job process, know that there is fear talking. So, when they begin to understand why they are having difficulty moving forward in the process, they can finally identify the fear and be ready to move on with full of confidence to achieve their dreams. To overcome the barriers, think like the employers you want to work for, identify and prove you are an ideal candidate in terms of ability as well as presentation, dependability, motivation attitude, and social network too. Therefore, this article will cover on three main obstacles of graduates in hiring jobs so that everyone can determine their weaknesses and come up with an action plan to carry forward their life and achieve what they want.